Measuring economic competence of secondary school students in Germany. Issue 3 (26th August 2020) - Kaiser, Tim; Oberrauch, Luis; Seeber, Günther
Abstract: The authors introduce a test of economic competence for German-speaking secondary school students and provide evidence from a large-scale assessment with 6, 230 students from grades 7 to 10. They present the development and psychometric properties of the scale, along with an investigation of predictors of economic competence. They find evidence of a gender gap favoring male students, lower scores for students with a migration background, and parents' socioeconomic background being a predictor of test performance. Additionally, the authors document sizeable differences between tracks, as well as gains in economic competence across grades in the order of magnitude of 0.06 to 0.20 standard deviation per year. The article concludes with perspectives on an impact evaluation of a curriculum reform introducing mandatory economic education in secondary school.